Communication Patterns in the Perspective of Dramaturgical Theory - Nahdatunnisa Asry; Lisda Ariani Simabur; Wahyuni Bailussy (Palakka : Media and Islamic Communication, 2022)
Dramaturgy is a view of social life as a series of drama performances in a stage. The term Dramaturgy is thick with the influence of drama or theater or fictional performances on stage where an actor plays other human characters so that the audience can get a picture of the life of the character and be able to follow the storyline of the drama being presented. Dramaturgy can be seen from the way a person communicates. Effective communication can affect other people's perceptions of us. We want other people to give good judgment, at least have the impression that we are consistent with the purpose of communicating to them. The purpose of this study is to describe communication patterns in the perspective of dramaturgical theory. The methodology used is a descriptive qualitative approach to the literature study method. The results of this study indicate that effective communication patterns can influence other people's perceptions of us. When humans interact with each other, they want to manage the impression that they hope to grow on other people towards them. For this reason, everyone performs for others, which is called the dramaturgical approach. This action is actually very natural, meaning that it is not always an attempt to pretend or deceive other people. Because even though some of our behavior may be pretend, we also know that we have different social roles for different people and situations, which will affect our behavior when communicating